(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article proposes a reflection about a collection of ukiyo-e from the Archivo Central Andrés Bello of the Universidad Chile. The breadth of the problem is extended on two exploratory constellations: on the one hand, to inquire the controversy, apparently, to interrogate the Japanese object from Western disciplinary logics (paradigms), that means, through the West-East dichotomy. On the other hand, to characterize how this initial tension was neglected or inverted, as a social paradigm on ukiyo-e, and with it, the principle of associativity of the images in the space of the (local) museum.